PERFORMA BUKAAN SELUBUNG FASAD RUMAH PANGGUNG VERNAKULAR TERHADAP KENYAMANAN TERMAL PENGHUNI - Prihatiningrum, Atik; Ramawangsa, Panji Anom (Jurnal Arsitektur ARCADE, 2022)
Abstract: Thermal conditions in buildings in residential houses include temperature, humidity, and wind speed that enter the dwelling which is influenced by the area of the openings in the facade of the building. Seeing the existing problems, the purpose of this research is to investigate the performance of the facade cladding on the Rejang tribal stilt houses using the software simulation method. This is done to obtain the thermal value for the occupants of the stilt house so that several factors are obtained that affect the quality of the thermal value in the space in the stilt house. The research methodology is divided into several stages, namely collecting data on room temperature, air humidity, and wind speed in the house that is the object of research, and data analysis using Google Sketchup Sefaira software and the Center For The Built Environment (CBE). The results obtained are that the thermal comfort conditions of the occupants of the house have a variety of sensations that are influenced by the activities of the occupants and the type of clothing. In addition, the condition of the openings on the windows and doors of the stilt houses and the orientation of the building to the path of the sun affect the indoor temperature conditions, humidity, and wind speed flowing into the room.Abstrak: Kondisi termal di dalam bangunan pada rumah tinggal meliputi suhu, kelembaban, dan kecepatan angin yang masuk ke dalam rumah tinggal dipengaruhi oleh luas bukaan yang ada di selubung fasad bangunan. Melihat permasalahan kondisi eksisting yang ada, maka tujuan penelitian ini untuk menelusuri performa selubung fasad pada rumah panggung suku Rejang dengan menggunakan metode simulasi software.Â  Hal ini dilakukan untuk mendapatkan nilai termal pada penghuni rumah panggung sehingga didapatkan beberapa faktor yang mempengaruhi kualitas nilai termal pada ruang dalam rumah panggung.Â  Metodologi penelitian terbagi dari beberapa tahap, yaitu pengumpulan data suhu ruang, kelembaban udara, dan kecepatan angin di dalam rumah yang menjadi objek penelitian, dan analisis data dengan menggunakan software Google Sketchup Sefaira dan Center For The Built Environment (CBE). Hasil yang didapatkan adalah kondisi kenyamanan termal penghuni rumah memiliki ragam sensasi yang dipengaruhi oleh aktifitas penghuni dan jenis pakaian. Selain itu kondisi bukaan pada jendela dan pintu rumah panggung serta orientasi bangunan terhadap jalur lintas matahari mempengaruhi kondisi suhu ruang dalam, kelembaban udara, dan kecepatan angin yang mengalir ke dalam ruangan.